2013
DOI: 10.1016/j.jval.2013.03.1095
|View full text |Cite
|
Sign up to set email alerts
|

Development Of Patient-Reported Outcomes (Pro) And Observer-Reported Outcomes (Obsro) Measures For Pediatric Ulcerative Colitis: Concept Elicitation Findings

Abstract: surgery occurred a mean of 4.2±2.5 years ago. Based on the HADS, 31% and 16% of patients had clinically meaningful anxiety and depression, respectively. Depression was significantly associated with poorer totaI IBDQ scores (p<0.0001) and higher BIQ scores (p<0.0001). Females are 2.15 times more likely to have anxiety than males (OR 2.15, 95% CI 1.19-3.88). Other factors associated with anxiety include loss of work productivity (OR 1.39, 95% CI 1.18-1.64) and poorer body image (OR 1.12, 95% CI 1.04-1.20). CONCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a comparison of semi-structured interviews with blogs for purposes of PRO development, Acaster and Wild [12] reported a high degree of convergence about symptoms experienced by women with menopausal hot flashes, with no major discrepancies in themes elicited between the two methods. In a study eliciting concepts among children from ulcerative colitis, Yen et al [13] used blogs to substantiate concepts identified through traditional interviews and found these data to be supportive. This area is still developing, however, and the most recent ISPOR PRO Good Practices Task Force guidance makes no mention of data gathered online [14].…”
Section: Benefits Of Social Media For Pro Concept Elicitationmentioning
confidence: 99%
“…In a comparison of semi-structured interviews with blogs for purposes of PRO development, Acaster and Wild [12] reported a high degree of convergence about symptoms experienced by women with menopausal hot flashes, with no major discrepancies in themes elicited between the two methods. In a study eliciting concepts among children from ulcerative colitis, Yen et al [13] used blogs to substantiate concepts identified through traditional interviews and found these data to be supportive. This area is still developing, however, and the most recent ISPOR PRO Good Practices Task Force guidance makes no mention of data gathered online [14].…”
Section: Benefits Of Social Media For Pro Concept Elicitationmentioning
confidence: 99%